Dissimilar local risk factors among patients diagnosed with cystic echinococcosis upon voluntary screening in highly endemic regions of Kyrgyz Republic - Kursanbek M. Raimkulov; Vera S. Toigombaeva; Omurbek T. Kuttubaev; Zhyldyz S. Smailbekova; Asel D. Adambekova; Maria N. Ruzina; Lyudmila V. Akhmadishina; Alexander N. Lukashev (Parasitology)
Echinococcosis is a parasitic invasion caused by a cestode of the genus Echinococcus. Kyrgyzstan is a country in Central Asia known for an extremely high incidence of echinococcosis. A total of 10 093 subjects were screened in the Osh, Naryn and Batken regions of Kyrgyzstan in 2015–2017 by ultrasound and questioned for potential risk factors. Cystic echinococcosis (CE) prevalence (combined newly diagnosed and post-surgery cases) ranged between 0.2 and 25.2% across the study regions. Typical factors, such as dog or livestock ownership, weakly affected CE risk (odds ratio [OR] = 1.18–1.83). Use of water from a well and owning a cat had a greater effect on CE risk (OR = 2.02–2.28). The risk factors of CE were highly dissimilar among the study regions, with patterns not always compatible with classical biohelminthosis transmission routes (no risk from livestock in certain areas, significant risk from using well water, owning cats). Therefore, the CE epidemic in Kyrgyzstan is not holistic in terms of potential mechanisms and risk factors, and certain areas can greatly benefit from preventive measures that will have limited efficiency elsewhere.